2022
DOI: 10.1002/smll.202203259
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impurities from Manufacturing Process on the Toxicity Profile of Boron Nitride Nanotubes

Abstract: The toxicity of boron nitride nanotubes (BNNTs) has been the subject of conflicting reports, likely due to differences in the residuals and impurities that can make up to 30–60% of the material produced based on the manufacturing processes and purification employed. Four BNNTs manufactured by induction thermal plasma process with a gradient of BNNT purity levels achieved through sequential gas purification, water and solvent washing, allowed assessing the influence of these residuals/impurities on the toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 93 publications
(138 reference statements)
0
15
0
Order By: Relevance
“…Therefore, this study highlighted that the shape of 2D materials is an important physicochemical parameter influencing the biological interaction with cells . In another in vitro study using the macrophage-derived THP-1 human cell line, Kodali et al, have shown that both BNNTs and h -BN induced biological responses 24 h after exposure . They found that h -BN and BNNTs caused significant increases in the secretion of several pro-inflammatory cytokines, including IL-1β and GM-CSF with some of them secreted in response to BNNTs, but not to h -BN .…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Therefore, this study highlighted that the shape of 2D materials is an important physicochemical parameter influencing the biological interaction with cells . In another in vitro study using the macrophage-derived THP-1 human cell line, Kodali et al, have shown that both BNNTs and h -BN induced biological responses 24 h after exposure . They found that h -BN and BNNTs caused significant increases in the secretion of several pro-inflammatory cytokines, including IL-1β and GM-CSF with some of them secreted in response to BNNTs, but not to h -BN .…”
Section: Introductionmentioning
confidence: 80%
“…18 They also found less cytotoxicity for h-BN and impure BNNTs (low amount of nanotubes per mass) than for pure BNNTs (high amount of nanotubes per mass). 18 Observing less toxicity for low aspect ratio h-BN nanosheets in comparison to high aspect ratio BNNTs agrees with the fiber pathogenicity paradigm and definition of high aspect ratio nanomaterials. It is well accepted that high aspect ratio materials, with a length above 5 μm and a ratio "lengthdiameter/thickness" greater than 3, could cause chronic lung toxicity and permanent damage after lung administration if they reached the alveolar region and induced frustrated phagocytosis in alveolar macrophages.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…BNNTs have potential for self-cleaning and anticorrosive surfaces . Owing to BNNTs biological compatibility and reduced toxicity to cells compared to carbon nanotubes, there are many application arenas for BNNTs beyond the realm of industrial materials, including biological and clinical environments, such as in drug carrier design and cancer therapeutics . Despite the time since the first demonstration of BNNTs and their remarkable collection of properties, progress in their development has been slow.…”
Section: Introductionmentioning
confidence: 99%